Seroprevalence of molluscum contagiosum virus in German and UK populations - Sherwani, Subuhi; Farleigh, Laura; Agarwal, Nidhi; Loveless, Samantha; Robertson, Neil; Hadaschik, Eva; Schnitzler, Paul; Bugert, Joachim J. (PLOS ONE, 2014)
Molluscum contagiosum virus (MCV) is a significant but underreported skin pathogen for children and adults. Seroprevalence studies can help establish burden of disease. Enzyme linked immunosorbent assay (ELISA) based studies have been published for Australian and Japanese populations and the results indicate seroprevalences between 6 and 22 percent in healthy individuals, respectively. To investigate seroprevalence in Europe, we have developed a recombinant ELISA using a truncated MCV virion surface protein MC084 (V123-R230) expressed in E. coli. The ELISA was found to be sensitive and specific, with low inter- and intra-assay variability. Sera from 289 German adults and children aged 0-40 years (median age 21 years) were analysed for antibodies against MC084 by direct binding ELISA. The overall seropositivity rate was found to be 14.8%. The seropositivity rate was low in children below the age of one (4.5%), peaked in children aged 2-10 years (25%), and fell again in older populations (11-40 years; 12.5%). Ten out of 33 healthy UK individuals (30.3%; median age 27 years) had detectable MC084 antibodies. MCV seroconversion was more common in dermatological and autoimmune disorders, than in immunocompromised patients or in patients with multiple sclerosis. Overall MCV seroprevalence is 2.1 fold higher in females than in males in a UK serum collection. German seroprevalences determined in the MC084 ELISA (14.8%) are at least three times higher than incidence of MC in a comparable Swiss population (4.9%). While results are not strictly comparable, this is lower than Australian seroprevalence in a virion based ELISA (n = 357; 23%; 1999), but higher than the seroprevalence reported in a Japanese study using an N-terminal truncation of MC133 (n = 108, 6%; 2000. We report the first large scale serological survey of MC in Europe (n = 393) and the first MCV ELISA based on viral antigen expressed in E. coli.
Gesehen am 24.09.2020